MLB Announcer and Baseball Executive Victor Rojas (Thirty Minute Mentors). - Mendler | Thirty Minute Mentors, Adam (linkedin.com, 2022)
Learn lessons on entrepreneurship, leadership, and communication from Victor Rojas, a former MLB announcer and sports executive.